A case of solitary fibrous tumor/hemangiopericytoma in the central nervous system with papillary morphology. Issue 2 (12th March 2019) - Cao, Lijuan; Zhang, Xialing; Wang, Yin; Bao, Yun; Tang, Feng
Abstract : This report describes the clinicopathological findings of a solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) of the central nervous system in a 59‐year‐old man with space‐occupying lesions on both the left anterior basicranial and on the top tail of falx cerebri. The tumor showed small quantities of solid papillary areas and a prominent papillary structure, where atypical cells were compactly arranged along the fibrovascular core. The tumor cells of both components showed nuclear relocalization of the signal transducer and activator of transcription 6 protein, with very high specificity and sensitivity for the diagnosis of SFT/HPC. In the literature, only three cases of SFTs with a papillary pattern have been reported, but this case showed a complete papillary pattern. "Papillary" SFT/HPC is a rare morphological variant of SFTs/HPCs, and its differential diagnosis among intracranial tumors is an important factor which clinicians should bear in mind during diagnosis.